Effects of Canine IL-12 on the Immune Response Against the Canine Parvovirus VP2 Protein - Shiyan Wang; Wenjie Jiao; Dannan Zhao; Yuzhu Gong; Jingying Ni; Huawei Wu; Jige Du; Tuanjie Wang; Chunsheng Yin (Vaccines)
Background: Canine parvovirus (CPV) is a highly pathogenic virus that predominantly affects puppies, with mortality rates exceeding 70%. Although commercial multivalent live attenuated vaccines (MLV) are widely employed, their efficacy is often compromised by maternal antibody interference. Consequently, the development of novel vaccines remains imperative for effective CPV control. Methods: Recombinant CPV VP2 protein (rVP2) and canine interlukine 12 protein (rcIL-12) were expressed using the Bac-to-Bac baculovirus expression system and the biological activity of these proteins was assessed through hemagglutination, Cell Counting Kit-8 (CCK8) and IFN-γ induction assays. The combined immunoenhancement effect of rVP2 and rcIL-12 protein was evaluated in puppies. Results: Both rVP2 and rcIL-12 were successfully expressed and purified, exhibiting confirmed antigenicity, immunogenicity, and bioactivity. Co-administration of rVP2 with rcIL-12 elicited higher neutralizing antibody titer (6–7 times higher), complete challenge protection efficiency (no clinical symptoms and tissue and organ lesions), fewer viral shedding (decreasing significantly 8-day post challenge) and superior viral blockade (lower viral load in the organism) compared to rVP2 alone. Conclusions: Our findings demonstrate that rVP2 co-administered with rcIL-12 induces robust protective immunity in puppies and significantly mitigated the inhibitory effects of maternal antibodies. This represents a promising strategy for enabling earlier vaccination in puppies and rational design of CPV subunit vaccines.